2010
DOI: 10.1016/j.molcel.2010.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A WD-Repeat Protein Stabilizes ORC Binding to Chromatin

Abstract: SUMMARY Origin recognition complex (ORC) plays critical roles in the initiation of DNA replication and cell-cycle progression. In metazoans, ORC associates with origin DNA during G1 and with heterochromatin in postreplicated cells. However, what regulates the binding of ORC to chromatin is not understood. We have identified a highly conserved, leucine-rich repeats and WD40 repeat domain-containing protein 1 (LRWD1) or ORC-associated (ORCA) in human cells that interacts with ORC and modulates chromatin associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(174 citation statements)
references
References 69 publications
4
168
2
Order By: Relevance
“…Several examples include E2F and Myb transcription factors, which interact with ORC and target it to the origin at chorion amplification locus in Drosophila (35,36). Recent studies revealed the role of HMG1A and WD repeat-containing LRWD1 proteins in targeting of ORC to the chromatin in human cells (28,37). Interestingly, human Orc6 and HMG1A proteins interact directly and may both contribute to the targeting of ORC to the sites of replication initiation and to the pre-RC assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Several examples include E2F and Myb transcription factors, which interact with ORC and target it to the origin at chorion amplification locus in Drosophila (35,36). Recent studies revealed the role of HMG1A and WD repeat-containing LRWD1 proteins in targeting of ORC to the chromatin in human cells (28,37). Interestingly, human Orc6 and HMG1A proteins interact directly and may both contribute to the targeting of ORC to the sites of replication initiation and to the pre-RC assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Structure-guided mutations that abrogated H4K20me2 binding by ORC1 were defective in binding to known origins, and cells expressing these mutants showed a delay in progressing through G 1 -phase (23). In addition to ORC1, another factor present in the ORC complex, named ORCA/LRWD1, binds to H4K20me3 via its WD repeat domain (64,66), suggesting that H4K20me2 and H4K20me3 may be involved in stabilizing the ORC complex at ORIs via direct binding to the key ORC component proteins ORC1 and ORCA. Mutations within several factors that comprise the pre-DNA replication machinery have been identified in individuals affected by Meier-Gorlin syndrome (MGS), an autosomal recessive primordial dwarfism disorder (67)(68)(69)(70).…”
Section: Figmentioning
confidence: 99%
“…Perhaps the most intriguing potential mechanism of ORC localization is the recognition of specifically modified nucleosomes. Human ORC binds a protein called ORCA or LRWD1 that interacts with methylated nucleosomes that are associated with heterochromatin, suggesting an alternative method to localize ORC to compacted chromatin (Bartke et al 2010;Shen et al 2010;Vermeulen et al 2010). In addition, the amino terminus of the Orc1 protein contains a conserved bromo-adjacent homology (BAH) domain.…”
Section: Origin Recognitionmentioning
confidence: 99%